Tableting and stability evaluation of enteric-coated omeprazole pellets - (:unkn) unknown (ELSEVIER SCIENCE BV, 2004)
In this study, fluidized-bed manufactured enteric-coated omeprazole pellets were compressed into tablets. The stability of the pellets and those of compressed tablets were evaluated for remaining omeprazole and for degradation products under an accelerated stability protocol. The data were analyzed using the artificial neural network (ANN) and analysis of variance (ANOVA). It was found that enteric-coated omeprazole pellets could be compressed into quickly disintegrating tablets using microcrystalline cellulose granules as the pressure absorbing matrix. The ANN, using the multilayer perceptron model, predicted that there was a positive correlation between tablet crushing strength and microcrystalline cellulose concentration. Microcrystalline cellulose matrix showed a strong plastic deformation and all the pellets inside the tablet maintained their integrity with no significant change in their surface properties. Omeprazole degradation in acid medium was mainly dependent on microcrystalline cellulose concentration. A 90-day accelerated stability test in brown glass bottles with a desiccant showed that all prototype formulations would result in an acceptable stability profile for both remaining omeprazole, and also for the increase of impurity concentrations. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: pellets; artificial neural networks; pellet compression; omeprazole; accelerated stability; COMPRESSION; PRODUCTS